Morphological and molecular characterization of five Colletotrichum species from India - R. AGGARWAL*; D.K. AGARWAL, H.T. ROHANA WIJESEKARA (Indian Phytopathology, 2005)
Twenty Colletotrichum isolates comprising of five species C. capsici. C. dematium, C. falcatum, C. gloeosporioides and C. lindemuthianum from different geographical locations of India (New Delhi 4, Sikkim 2, Solan 3, Pantnagar 3, Daurala 2, Culcutta 1, Lucknow 1, Navasari 1, Pune 1, Dapoli 1 and Karnal 1) isolated from different crops (sugarcane, bell pepper, lal mirich, Gomphrena, Melia, bottle brush, Passiflora foetida, ashwagandha, egg plant, grape, cattleya, cashew nut, French bean, and soybean) were analyzed with RAPD markers. Morphological and cultural characters of these different species were correlated with the RAPD data. PCR amplification of total genomic DNA with 16 random primers generated unique banding patterns depending upon primer and the isolate. Sugarcane isolates 4800 and 4803 produced identical banding pattern while other isolates produced dissimilar bands within the particular species indicating the genetic diversity among the isolates within a species. Morphological characters were also different from each other even in sugarcane isolates 4800 and 4803, which shared identical bands. Cluster analysis also indicated a very high degree of genetic variability within a given Colletotrichum species. C. capsici and C. dematium isolates clustered together in the dendrogram showing their genetic relatedness. Morphological characters also supported this clustering. RAPD markers were better suited for differentiating isolates within a species rather than species.